Coping as a moderator of the influence of economic stressors on psychological health - Jesus,Saúl Neves (2016)
Since 2008, there has been a decline in the economy of several European countries, including Portugal. In the literature, it is emphasized that periods of economic uncertainty propitiate the appearance of mental health problems and diminish populations well-being. The aim of the present study, with 729 Portuguese participants, 33.9% (n=247) males and 66.1% (n=482) females with an average age of 37 years old (M=36.99; SD=12.81), was to examine the relationship between economic hardship, financial threat, and financial well-being (i.e., economic stressors) and stress, anxiety, and depression (i.e., psychological health indicators), as well as to test the moderation effect of coping in the aforementioned relationship. To achieve these goals, a cross-sectional design was implemented and structural equation modeling (SEM) was used to analyze the obtained data. Our results underline that coping affects the relationship between economic stressors and psychological health since subjects with lower coping levels are more vulnerable to economic stress factors than those with higher coping levels. The moderation effect was more evident in the relationships between economic hardship and stress, anxiety, and depression. The main implications of this study are presented, as well as its limitations and suggestions for future research.